Penggunaan Media Instagram @Fannanvisuals dalam Promosi Wedding Documentation - Fery Abdul Pradana; Erman Anom; Iswadi Iswadi (IPM2KPE, 2023)
This study aims to find out the impact of using Instagram media @fannanvisuals in promoting wedding documentation. The research method used is a qualitative research method with a case study type. The data collection techniques used are interviews, observation, and documentation. The results of the research that has been done show that the use of social media Instagram by Fannanvisuals as the main marketing tool has a pretty good impact. By leveraging features such as hashtags, geo-location, stories, and collaboration with related accounts, Fannanvisuals can expand their promotional reach and increase their brand awareness among potential customers. In conclusion, if it is important for a company or other agency to adapt a social media marketing strategy in accordance with the characteristics of the target market and business goals to achieve optimal results. Keywords: Instagram, Media, Promotion, Wedding Documentation